Estudio de factibilidad para el montaje de una empresa productora y comercializadora de arequipe de pepa de pan en el municipio de Buenaventura (2011)
The Business Plan is based on the creation of a producer and marketer of nugget bread caramel (dulce de leche-based Pan Pepa) in the municipality of Buenaventura, which analyzes the opportunity to industrialize the process of development of poorly operated in the Pacific area which currently is handled in a traditional way, in order to generate interest and changes that promote the exploitation and marketing of fruit Pan Pepa adding to this process, the adoption of technology to be competitive in the market for sweets. In the course of the investigation evaluated the environment of the craft of sweets, defined variables involved in the actual production and marketing and how to allocate resources optimally, investment and manpower to implement the project. Could be detected if the bread Pepa is still marketing the way they currently get, not be possible to industrialize its production process and creation of new products resulting in the loss of economic potential. It is convenient to design a business plan to support the idea of industrializing the production process, analyzing product demand and market potential which could be accessed, given that this is a remarkable product, characteristic and whose raw material is economically easier to obtain. But in the course of the investigation concluded that in order to achieve an industrial process of Arequipe de pepa de pan requires a great investment and it is a long-term taking into account that it must start from the fact that matter main raw is not harvested but occurs in the wild and should be access to new technology.